2019
DOI: 10.1556/1886.2018.00033
|View full text |Cite
|
Sign up to set email alerts
|

Screening for carbapenemases in ertapenem-resistant Enterobacteriaceae collected at a Tunisian hospital between 2014 and 2018

Abstract: Background Carbapenem-resistance is frequently detected in Enterobacteriaceae isolated from patients in Tunisia. The study was performed to identify frequent carbapenemases in Tunisian isolates. Methods Between May 2014 and January 2018, 197 ertapenem-resistant Enterobacteriaceae were isolated at the microbiological department of the Military Hospital of Tunis. The strains were phenotypically characterized and then s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 43 publications
10
33
1
Order By: Relevance
“…Among the ve genes which were detected by multiplex PCR, the most encountered gene was OXA-48like at a genotypic frequency of 36.4%. This corroborates well with recent studies which documented OXA-48-like gene and its variants as the most prevalent genes [27,31,33,35]. OXA-48.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among the ve genes which were detected by multiplex PCR, the most encountered gene was OXA-48like at a genotypic frequency of 36.4%. This corroborates well with recent studies which documented OXA-48-like gene and its variants as the most prevalent genes [27,31,33,35]. OXA-48.…”
Section: Discussionsupporting
confidence: 93%
“…OXA-48 producers spread sporadically to the neighboring countries located in the southern and eastern part of the Mediterranean Sea, and north Africa [36]. This provides an insight why the occurrence of OXA-48 is predominantly high in Egypt and Tunisia [27,33]. Previous studies reported NDM as the most dominant gene in South Africa [30,37], VIM and IMP as the most prevalent genes in East Africa [23][24][25]38] in contrast with the results of this study.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…KPC, VIM, NDM, OXA-48 and IMP are the commonest carbapenemases worldwide [42]. Findings of this study revealed the existence of all those carbapenemases encoding genes in Uganda and OXA-48 was the most predominant gene in contrast with previous studies in the region [18,25] but in agreement with recent studies in carried out in Africa ( [31,33,36,40]. OXA-48 carbapenemase was rst detected in Turkey and it became epidemic in the Middle East and Mediterranean countries [41].…”
Section: Discussionsupporting
confidence: 87%
“…This genotypic carbapenem resistance prevalence corroborates with earlier studies conducted in the East African region [18,25,38] and elsewhere [27,39] that reported levels ranging from 25% to 40%. Contrary, this frequency is signi cantly lower than carbapenem genotypic levels reported by studies in Tunisia (76.7%) [40], South Africa (68% and 86%) [33,34] , Egypt (89.6%) [37], Turkey (49.5%) [41]. KPC, VIM, NDM, OXA-48 and IMP are the commonest carbapenemases worldwide [42].…”
Section: Discussionmentioning
confidence: 76%